2014
DOI: 10.1111/jog.12282
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of acute fatty liver of pregnancy from syndrome of hemolysis, elevated liver enzymes and low platelet counts

Abstract: As proposed criteria (Swansea criteria) for the diagnosis of acute fatty liver of pregnancy (AFLP) do not include antithrombin (AT) activity, diagnosis of AFLP may be delayed. The aim of this review is to underscore problems in the differential diagnosis of AFLP and the syndrome of hemolysis, elevated liver enzymes and low platelet counts (HELLP syndrome) and to facilitate prompt diagnosis of AFLP. Published works dealing with liver dysfunction in pregnancy, HELLP syndrome and AFLP were reviewed. AFLP and HELL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0
15

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 85 publications
(223 reference statements)
2
56
0
15
Order By: Relevance
“…More than 60% of cases of PIATD occur, however, in the absence of HDP, similar to the lack of preceding HDP in approximately half of AFLP patients . In addition, half of AFLP patients lack thrombocytopenia at presentation . Therefore, although neither HDP nor thrombocytopenia was present initially in this patient, the present patient was carefully monitored and found to have depressed AT activity, with a decrease to 41% of normal, concomitant with the development of pre‐eclampsia 8 days prior to delivery.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…More than 60% of cases of PIATD occur, however, in the absence of HDP, similar to the lack of preceding HDP in approximately half of AFLP patients . In addition, half of AFLP patients lack thrombocytopenia at presentation . Therefore, although neither HDP nor thrombocytopenia was present initially in this patient, the present patient was carefully monitored and found to have depressed AT activity, with a decrease to 41% of normal, concomitant with the development of pre‐eclampsia 8 days prior to delivery.…”
Section: Discussionsupporting
confidence: 48%
“…Given that HELLP syndrome is likely to occur in patients with pre‐eclampsia, physicians may monitor platelet count in such cases. More than 60% of cases of PIATD occur, however, in the absence of HDP, similar to the lack of preceding HDP in approximately half of AFLP patients .…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…There is disagreement in the published literature regarding the symptoms and clinically common manifestations reported, in general, which includes malaise, anorexia, nausea, vomiting, abdominal pain, jaundice, ascites, hypertension and abdominal distension. (4,(12)(13)(14)17) We found that anorexia, nausea, vomiting and abdominal pain were the main prodromic symptoms while progressive jaundice and ascites were common signs.…”
Section: Discussionmentioning
confidence: 95%
“…(10) Simultaneously, neonatal mortality rate has also decreased, which is in the range of 7% to 66%. (3,11) Previous clinical studies on AFLP, largely based on a few patients due to its low prevalence, have found large variations in results vis-à-vis its epidemiology, (2)(3)(4)(5)(6) symptoms, (12) complications (12) and outcomes. (3,10,11,13) For instance, Cheng et al (14) found that, besides aetiology, other clinical characteristics of pregnancy (e.g.…”
Section: Introductionmentioning
confidence: 99%